2015
DOI: 10.1007/s10585-015-9697-2
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of metastasis and outcome in patients with breast cancer

Abstract: There is growing evidence about differences in metastatic spread among breast cancer (BC) biologic subtypes (BS). Aim of this study was to analyze the pattern of metastasization according to BS and to explore the corresponding prognosis. A series of 544 consecutive patients receiving anticancer therapy for metastatic BC from 2004 to 2013, was analyzed. BS were defined by immunohistochemistry according to St Gallen 2013 criteria. Association between BS and the different distant localizations was analyzed. Progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
158
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(185 citation statements)
references
References 20 publications
19
158
1
7
Order By: Relevance
“…Bone metastasis is the most common metastasis of breast cancer, but the predictive value of BCS for bone metastasis is still controversial. Previous studies have tended to suggest that HR+ patients are more prone to bone metastases [19, 2224]. Our results also showed that the probability of bone metastasis in patients with HR+ subtypes (HR+/HER2− and HR+/HER2+) was significantly higher than that for patients with HR− subtypes (HR−/HER2− and HR−/HER2+).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Bone metastasis is the most common metastasis of breast cancer, but the predictive value of BCS for bone metastasis is still controversial. Previous studies have tended to suggest that HR+ patients are more prone to bone metastases [19, 2224]. Our results also showed that the probability of bone metastasis in patients with HR+ subtypes (HR+/HER2− and HR+/HER2+) was significantly higher than that for patients with HR− subtypes (HR−/HER2− and HR−/HER2+).…”
Section: Discussionsupporting
confidence: 70%
“…Park et al found that BCS did not affect the OS of patients with early recurrence (distant metastases within 24 months after surgery; P = 0.08), but for patients with distant metastases ≥24 months after surgery, BCS significantly affected the OS, and the survival of HR+/HER2− and HR−/HER2+ patients was superior to that of the HR+/HER2+ and HR−/HER2− groups (P < 0.001) [18]. Considering the St Gallen molecular subtypes (2013), Gerratana et al found that the median survival time for luminal HER2+ was 56.7 months, luminal A 45.3 months, luminal B 31.1 months, non-luminal HER2+ 21.5 months, and TNBC 9.3 months (P < 0.0001) [19]. Based on our results and related studies, BCS has both prognostic value for newly diagnosed and advanced breast cancer patients, and can also predict the patterns of distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…23 The HER2C subtype was also found to display a higher risk of developing liver metastasis. 21,24 Most recently, a SEER database analysis indicated that patients with TNBC, especially BLBC, primarily presented with lung metastasis. However, there was no difference in the total probability of lung metastasis across all subtypes.…”
Section: Clinical Features Of Metastasis In Breast Cancermentioning
confidence: 99%
“…Additionally, patients with distant metastatic disease have a significantly shorter survival time relative to the other breast cancer subtypes [4]. The most common ectopic sites for TNBC to metastasize are the lungs, the liver, bones and the brain [5] with a higher propensity of metastasis to the lungs [3, 6]. Currently there is an unmet and compelling need for novel approaches to treat patients with metastatic TNBC.…”
Section: Introductionmentioning
confidence: 99%